The Marriage of Mademoiselle Beulemans Based on a Play by Jean François Fonson and Fernand Wicheler - Dalpane, Marco; Fonson, Jean François; Wicheler, Fernand (Cinema of Discovery: Julien Duvivier in the 1920s, 2021)
Set in Brussels, where Suzanne Beulemans, the daughter of a rich brewer is promised to marry Séraphin Meulemeester, the son of a rival brewer. The young man and his father both seem particularly motivated by the dowry of the young fiancée. But Séraphin has a rival in Albert Delpierre, a young Frenchman who is learning brewery from Ferdinand Beulemans and who is discreetly enamoured with the young woman. Albert learns Séraphin's secret that he is having an affair with a worker and that they have had a child. He promises Séraphin that he will never reveal any of it to Suzanne, but she is told by Isabelle, her maid. [letterboxd.com]